2021
DOI: 10.1371/journal.pone.0258932
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus (HBV), Hepatitis C Virus (HCV) and Human Immunodeficiency Virus (HIV) infections among undocumented migrants and uninsured legal residents in the Netherlands: A cross-sectional study, 2018–2019

Abstract: Background Migrants are not routinely screened for hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus (HIV) in the Netherlands. We estimated the prevalence and determined factors associated with HBV, HCV and/or HIV infections among undocumented migrants and uninsured legal residents. Methods In this cross-sectional study, undocumented migrants and uninsured legal residents were recruited at a non governmental organization (NGO), healthcare facility in the Netherlands and were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Regarding the outcomes, studies reported on higher SMM, higher pre-term and low-weight birth for newborns, higher incidence of HIV and even higher prevalence of AIDS across undocumented migrant populations. The latter was coupled with previously described risks of gender-based violence, female genital mutilation and human tra cking experienced by this population as part of their migratory journey, emphasizing the vulnerability of undocumented migrants to poor health outcomes; further accentuated by socio-economic disadvantages and poor living standards (13,24,35,50). Whilst no article reported on differences between genders, it would be interesting to study how different contexts of vulnerability to exploitation, sexual abuse and/or human tra cking play out for undocumented men and women to better assess their speci c needs and render targeted services.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Regarding the outcomes, studies reported on higher SMM, higher pre-term and low-weight birth for newborns, higher incidence of HIV and even higher prevalence of AIDS across undocumented migrant populations. The latter was coupled with previously described risks of gender-based violence, female genital mutilation and human tra cking experienced by this population as part of their migratory journey, emphasizing the vulnerability of undocumented migrants to poor health outcomes; further accentuated by socio-economic disadvantages and poor living standards (13,24,35,50). Whilst no article reported on differences between genders, it would be interesting to study how different contexts of vulnerability to exploitation, sexual abuse and/or human tra cking play out for undocumented men and women to better assess their speci c needs and render targeted services.…”
Section: Discussionmentioning
confidence: 83%
“…One of the most occurrent themes within the appropriateness dimension of access to SRHS for undocumented migrants in the present studies is the lack of coordination and continuity of care characterizing populations who are often on the move, lack stable living and housing conditions in the host countries, and who often navigate different layers of legality and illegality (33). This lack of continuity of care and treatment is most concerning in the presence of infectious diseases requiring obligatory treatment by public health authorities, such as the cases of HIV, HBV, or Hepatitis C Virus (HCV) (24). Often the lack of coordination and the disintegrated character of healthcare services means that patients who lack the necessary knowledge and might also be subject to fear and stigma will be lost to follow-up (35).…”
Section: Appropriatenessmentioning
confidence: 80%
See 3 more Smart Citations